126=x+92

Simple and best practice solution for 126=x+92 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 126=x+92 equation:


Simplifying
126 = x + 92

Reorder the terms:
126 = 92 + x

Solving
126 = 92 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
126 + -1x = 92 + x + -1x

Combine like terms: x + -1x = 0
126 + -1x = 92 + 0
126 + -1x = 92

Add '-126' to each side of the equation.
126 + -126 + -1x = 92 + -126

Combine like terms: 126 + -126 = 0
0 + -1x = 92 + -126
-1x = 92 + -126

Combine like terms: 92 + -126 = -34
-1x = -34

Divide each side by '-1'.
x = 34

Simplifying
x = 34

See similar equations:

| 2+6x=2+4x | | 26x=-78 | | -32x=96 | | -3x=108 | | -48x=96 | | -26x=104 | | c^2=-2c+45 | | x^2+2ax+a^2-9=0 | | -x=397 | | 41-7x=160 | | c^2=2c+16 | | 4(3x-1)=6(x-1) | | 23+x=19+11 | | 4x+3.75=x-6 | | Y=7/17 | | 11.3y=4052 | | (2y-5x-4)-(x-6y+5)= | | 38-4=8 | | 8(x)+10=-9 | | x+78=97 | | 8(x)+10=9 | | x-(-53)=-123 | | (-3x-y+2)+(-2x+4y-9)= | | x-(-62)=-54 | | -3(y+5)-21=0 | | 10+-18+15z+z= | | 3x-7/2=x/3 | | x-(-33)=-75 | | 3(y+5)-21=-0 | | -1.4+0.72=x | | x-(-87)=-34 | | logx+4(17-4)=2 |

Equations solver categories